OGBN P19 Tackling a post-COVID-19 cholecystectomy waiting list, are we meeting the challenge?. (7th December 2022) - Hamid, Mohammed; Mirtorabi, Neginsadat; Ghumman, Abdul; Khalid, Ayesha; Noor, Saleem; Kapoulas, Spyridon; Singhal, Rishi; Nijjar, Rajwinder; Richardson, Martin; Wiggins, Tom
Abstract: Background: The COVID-19 pandemic has led to a tremendous backlog in elective surgical activity, with over six million people on waiting lists and only 64% of patients meeting the 18-week elective standard. Our Hospital Trust adopted an innovative approach to dealing with elective waiting times for cholecystectomy during the recovery phase from COVID-19. This study aimed to evaluate trends in overall cholecystectomy activity and the effect on waiting times. Methods: A prospective observational study was undertaken investigating patients who received a cholecystectomy at large UK hospital Trust, between February 2021 and February 2022. There were multiple phased strategies to tackle a 533 patient waiting list: private sector, multiple sites including emergency operating, mobile theatre, and seven-day working. An additional 364 patients were added and 145 removed, for multiple reasons, from the list during the study period. Correlation of determination (R 2 ) and Kruskal-Wallis analysis were used to evaluate trends in waiting times across the study period. Results: 657 patients underwent a procedure, of which 628 (95.6%) were completed electively. The median age was 49 years, 602 (91.6%) patients had an ASA of 1–2, and 494 (75.2%) were female. Thirty (4.6%) patients were listed post gallstone pancreatitis, 380 (57.8%) for cholelithiasis, and 228 (34.7%) for cholecystitis. The median length of stay was zero days (IQR 0–1), with 30-day complication (C-D ≥3, 1.8%), readmission (3.0%) and mortality (0.0%) rates noted. The current waiting list includes 95 patients, with median waiting times reduced from 428 days (IQR 373–508) to 49 (IQR 34–96), R2=0.654, p<0.001. For pancreatitis specifically, waiting times have dropped from a median of 218 days (IQR 139–239) to 28 (IQR 24–40), R2=0.613, p<0.001. Conclusions: We have safely and effectively tackled the cholecystectomy waiting list locally utilising a number of phased strategies. Significant progress is being made towards once again meeting the gold-standard target for gallstone pancreatitis patients. The approach utilised here has potential to be adapted to other units, or other operation types in order to reduce elective waiting times.We have safely and effectively tackled the cholecystectomy waiting list locally utilising a number of phased strategies. Significant progress is being made towards once again meeting the gold-standard target for gallstone pancreatitis patients. The approach utilised here has potential to be adapted to other units, or other operation types in order to reduce elective waiting times.